Oxidative stress biomarkers response to high intensity interval training and relation to performance in competitive swimmers - Deminice, R.; Santana Trindade, C.; Carvalho Degiovanni, G.; Ribeiro Garlip, M.; Vannucchi Portari, G.; Teixeira M.; Jordao, A. A. (The Journal of Sports Medicine and Physical Fitness, 2010)
AIM: Aim of the study is to investigate the modulations of oxidative stress biomarkers and some antioxidants induced by high intensity interval training bout and its relation to swimming performance. METHODS: Ten swimmers performed a set of 8 maximal swims along 100 m by style of their specialty, with 10 minute for a rest. The concentration of blood lactate ([Lac]) was determined after each swim. The lactate tolerance index (LTI) was determined by the ratio between [Lac] and the respective times of execution of the 8 swims. The time to complete first 100 m swim at maximum effort (P100) and the international point score (IPS) reached in a specific competition were considered performance parameters. Venous blood was collected before and after the anaerobic training effort. RESULTS: Mean blood lactate concentration in the eight swims was 10.9 ± 1.2 mM. Significant increases were observed for TBARS (pre: 4.1±0.7 ?mol/L; post: 4.9±1.1. ?mol/L), CK (pre: 206.4±170.7 U/L; post: 244.4±176.9. U/L), GSH (pre: 0.52±0.06; post: 0.62±0.05. mM), and ascorbic acid (pre: 0.06±0.02; post: 0.11±0.03. mg/dL) after the anaerobic training bout compared to the values obtained before it. In addition, significant correlations (P < 0.05) were detected between LTI and P100 (r = -0.87) and IPS (r = 0.64) and between variation of ascorbic acid and P100 (r = -0.60). CONCLUSION: Anaerobic training bout proposed induces oxidative stress and cell muscle damage markers as well as modulates some antioxidants of competitive swimmers. The modulation of ascorbic acid seems to play an important role in the performance of these athletes.